Mediating effect of trust on supervisor on the relationship between individual factors and intention to whistle-blow in Malaysia - Mahmoud, Ibrahim (2018)
In Malaysia, government in its efforts to wrestle corruption and other malfeasance enacted Whistleblower Protection Act in order to encourage individuals to come forward and report misconducts. Despite this effort and huge amount of complaints received by enforcement agencies however, very few reports have protection and constitute whistleblowing. The majority of the reports were not regarded as protected disclosure. The main purpose of this study seeks to examine whether individual factors (personal responsibility of reporting, awareness and knowledge on whistleblowing, personal cost of reporting attitudes toward behavior and perceived behavioral control) influence the intentions of employees to whistleblow effectively in Malaysia, mediated by supervisor trust. The study employed survey research method where 158 useable questionnaires from working MBA students which were conveniently selected from five (5) business schools within Klang Valley Area have been retrieved for the analysis using SEM-PLS. Theory of Planned Behavior was used as underpinning theory, and supported by Social Exchange Theory and Graham model of Principled Organizational dissent respectively. Based on the specific objectives, the study reveals that majority of the respondents have moderate level of awareness and education of whistle-blowing. The study also finds that awareness and education of whistle-blowing, and personal responsibility of reporting are predictors of empolyees’ intentions to effective whistle-blow internally. However, personal responsibility of reporting, and personal cost of reporting have significant effect on employees’ intention to whistle-blow externally, while organizational commitment was found to be insignificant with the overall whistle-blowing intentions. Finally, the study showed that supervisor trust does not mediate the relationship between individual factors and intention to whistle-blow internally and externally. The study provides avenue for government and organizations to consider employees behavior when improving whistle-blowing policies. Limitations and recommendations for future research are highlighted.